Women Entrepreneurship as a Strategy for Sustainable Livelihoods - Tanusha Raniga (The Thinker)
Women establish their entrepreneurial projects for economic independence and to reduce vulnerability to poverty. The number of women engaged in entrepreneurial activities has increased as a result of access to business training and mentorship facilitated by non-governmental organisations. This paper advances empirical evidence in the field of social development and sustainable livelihoods. Using qualitative methodology, I present evidence from 20 women who were beneficiaries of a Non-Governmental Organisation’s entrepreneurship training in the province of Gauteng, South Africa. Underscored by the sustainable livelihood approach, this paper deliberates three connected themes: motivational factors that promote women entrepreneurs, nurturing social networks, and navigating financial capital challenges. The paper affirms women entrepreneurship as a positive social development strategy to assist unemployed women to work towards economic self-reliance.